2022
DOI: 10.1016/j.jcmgh.2021.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Reduction in Cholesterol 25-Hydroxylase Aggravates Diet-induced Steatosis

Abstract: Hepatic overexpression of cholesterol 25-hydroxylase or exogenous administration of 25-hydroxycholesterol (25-HC) in mice drastically reduced the high-fat diet-induced hepatic steatosis via massive production of bile acids. The underlying mechanism involves 25-HC activation of the liver X receptor-cytochrome P450 7A1 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…In terms of the process, HFD stimulates BA secretion to facilitate fat digestion [ 29 , 30 ], which is a major reason that ileal Fxr/Shp/Fgf15 signaling was remarkably increased in mice, regardless of tumor metastasis. Unlike previous findings that HFD hinders BA synthesis [ 31 , 32 ], our data revealed that HFD resulted in a distinct pattern in the hepatic BA synthesis between the NM and LM groups. NM mice exhibited a lowered BA synthetic level (a reduced Cyp7a1 expression with decrease of free BAs in liver and serum), which is in line with the activated intestinal feedback control signaling.…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of the process, HFD stimulates BA secretion to facilitate fat digestion [ 29 , 30 ], which is a major reason that ileal Fxr/Shp/Fgf15 signaling was remarkably increased in mice, regardless of tumor metastasis. Unlike previous findings that HFD hinders BA synthesis [ 31 , 32 ], our data revealed that HFD resulted in a distinct pattern in the hepatic BA synthesis between the NM and LM groups. NM mice exhibited a lowered BA synthetic level (a reduced Cyp7a1 expression with decrease of free BAs in liver and serum), which is in line with the activated intestinal feedback control signaling.…”
Section: Discussioncontrasting
confidence: 99%
“…Increased levels of cholesterol 25-hydroxylase (Ch25 h) and its enzymatic by-product 25HC in the liver prevent high-fat diet-induced hepatic steatosis. This beneficial mechanism involves the regulation of enterohepatic circulation of bile acids by the induction of the CYP7A1 gene via activation of LXR-α (Dong et al, 2022). Our data show that withaferin A also activates LXR-α and similarly induces its canonical target genes to that of 25HC and mimics and exerts similar effects on NAFLD.…”
Section: Discussionmentioning
confidence: 60%
“…Real-time PCR was performed with a total volume of 20 μl, which contained 2 μl of cDNA, 0.4 μl of each 10 μM forward and reverse primer, 5.2 ml of ddH2O and 10 μl of 2×PerfectStart® Green qPCR SuperMix (TransGen Biotech) on a CFX96 TM Real-Time PCR Detection System. PCR amplification was performed using cycling conditions of 94°C for 30 s, followed by 45 cycles of 94°C for 5 s and 60°C for 30 s. Relative gene expression changes were measured by the comparative Ct method, X = 2 -△△Ct ( Dong et al, 2022 ), using GAPDH as our housekeeping internal control gene. The primers used for qPCR are listed in Supplementary Table S3 .…”
Section: Methodsmentioning
confidence: 99%